Environmental and Social Impact Analysis of Industry on the Surrounding Communities in Bojonegara District, Serang, Banten - nafsiana, Gina; Dinda Khairurohmah; Enggar Utari; Nurhasanah; Liliana Novridasati (Banua: Jurnal Kesehatan Lingkungan, 2025)
Background: Concrete industry activities in Bojonegara County, Attack, Banten have potential environmental pollution which impacts the quality of the environment and public health. Community awareness of environmental issues also plays an important role in efforts to mitigate these impacts. Objective: to identify the level of noise and air pollution occurring around the Industry in Bojonegara, as well as its impact on the environment and surrounding communities. Method: This type of research is conducted with a descriptive approach that uses data collection techniques, including documentation, observations, and surveying. The indicator used is the New Ecological Paradigm (NEP) indicator. The NEP instrument consists of six indicators, namely rejection of anthropocentrism, awareness of vulnerable natural balances, the likelihood of ecological crises, rejection of exclusivity, growth limitations, and new community capabilities. Participants in this study included youth groups, RT chairs, and residents around the industry. Result: Research shows that youth groups have a higher environmental awareness than RT Chairs and other citizens, particularly in terms of anthropocentrism and the use of technology in addressing environmental issues. Meanwhile, RT groups showed relatively lower scores, indicating the need for an increase in environmental literacy at the local institutional level. Conclusion: The findings emphasize the importance of cross-generational, participatory, and transparent approaches in environmental policy making, including industrial development planning. It also stressed the importance of active coordination between industry and society to mitigate potential environmental damage through comprehensive environmental impact studies and all stakeholder engagement.